Spatial distribution patterns and movements of Holothuria arguinensis in the Ria Formosa (Portugal) - Siegenthaler, Andjin (2016)
Holothurian populations are under pressure worldwide because of increasing demand for beche-de-mer, mainly for Asian consumption. Importations to this area from new temperate fishing grounds provide economic opportunities but also raise concerns regarding future over-exploitation. Studies on the habitat preferences and movements of sea cucumbers are important for the management of sea cucumber stocks and sizing of no-take zones, but information on the ecology and behavior of temperate sea cucumbers is scarce. This study describes the small-scale distribution and movement patterns of Holothuria arguinensis in the intertidal zone of the Ria Formosa national park (Portugal).Mark/recapture studieswere performed to record theirmovements over time on different habitats (sand and seagrass). H. arguinensis preferred seagrass habitats and did not show a size or life stage-related spatial segregation. Its density was 563 ind. ha−1 and mean movement speed was 10 m per day. Movement speed did not differ between habitats and the direction of movement was offshore during the day and shoreward during the night. Median home range size was 35 m2 and overlap among home ranges was 84%. H. arguinensis' high abundance, close association with seagrass and easy catchability in the intertidal zone, indicate the importance of including intertidal lagoons in future studies on temperate sea cucumber ecology since those systems might require different management strategies than fully submerged habitats.